Analyzing the Challenges and Opportunities in Raising Public Awareness About the Hazards of Natural Disasters Among Junior High School Students in Bandung Regency, Indonesia - Amriwijaya, Julian; Tutty I. Sodjakusumah (HM Publisher, 2024)
Natural disasters pose a significant peril to the Indonesian community, especially the Bandung Regency. Due to the significant likelihood of calamities, it is crucial to enhance public consciousness, particularly among adolescents in junior high school, regarding the perils associated with natural catastrophes. The objective of this study is to examine the obstacles and possibilities of enhancing knowledge of natural disaster risks among middle school students in Bandung Regency. This study employs a qualitative methodology, utilizing a case study technique. The researchers gathered primary data by conducting interviews with junior high school students, instructors, and relevant stakeholders, in addition to making field observations. The research findings indicate that there are multiple obstacles to enhancing the level of awareness among junior high school students regarding the perils associated with natural disasters. These challenges encompass a deficiency in knowledge and comprehension concerning the hazards posed by natural disasters, limited availability of information and educational resources pertaining to disasters, indifference and a lack of concern towards natural disasters, as well as a dearth of proactive involvement from both educational institutions and parents. Nevertheless, this study has identified various avenues for enhancing the knowledge of junior high school students regarding the perils associated with natural calamities. These include incorporating disaster education into the school syllabus, employing information and communication technology (ICT) to disseminate information and educate about disasters, engaging students in simulation exercises and disaster response activities, and reinforcing the involvement of families and communities in fostering a culture of disaster awareness. Enhancing the knowledge and understanding of the potential hazards associated with natural disasters among junior high school students is a crucial measure to foster community resilience in the face of future calamities.